Prevalence of Stunting among 6-59 Months Children and its Association with Water, Sanitation and Hygiene Practice in Urban Slums of Kathmandu, Nepal - Singh, Sarswoti; Dhital, Nil P; Paudel, Rajan; Sah, Dipak K; Hamal, Arjun; Shrestha, Junu (Journal of Institute of Medicine Nepal, 2020)
Introduction Childhood malnutrition is a critical public health concern in Nepal. Slums are supposed to have poor water, sanitation and hygiene practices. This study has aimed to examine association between water, sanitation and hygiene (WASH) variables and stunting among 6 to 59 months children of slums of Kathmandu metropolitan city. Methods Descriptive cross-sectional study design was employed where 335 households were included in the study. Data were collected using standard questionnaire and observation checklist. Weight and height of children were taken using seca digital weighing scale and wooden height board of UNICEF respectively. Anthropometric analysis was done using WHO Anthro version 3.2.2 software and other statistical analysis was conducted using SPSSversion 22 software. Results The prevalence of stunting was 23%. Four out of five household (80%) in slum used to drink water from unimproved source. Absence of handwashing station (AOR=2.109, 95% CI:1.05-3.27) and absence of water storage covering (AOR=2.46, 95% CI: 1.16–5.23) were found to be significantly contributing to stunting status. Conclusion This study highlights the importance of good WASH practices, and the potential of WASH interventions, to contribute for the improved childhood stunting living in urban slums in Nepal. Also, the findings recommend the need of strategies on purification of water, improvement of toilets, behaviour change and awareness related activities to improve the stunting among children.